Development of educational hypermedia to teach an arterial blood pressure measurement procedure - Alavarce, Debora Cristina; Pierin, Angela Maria Geraldo (Revista da Escola de Enfermagem da USP, 2011)
Arterial blood pressure measurement is an essential conduct to evaluate the condition of the cardiovascular system. Digital teaching environment is a powerful tool for the teaching-learning process, because it adds meaning and concreteness to the content to be learned, and it can be useful to instruct this procedure. The objective of this study was to create educational hypermedia for teaching arterial blood pressure measurement, and to describe the steps of that creation process. The pedagogical framework of Robert Gagné was used; and the construction followed the model proposed by Price. The final product presents videos, photos, animations and simulations that demonstrate and teach the procedure. Although hypermedia construction has been difficult to use, it can positively enhance the teaching of nursing procedures.